Progression of malaria induced pathogenicity during chloroquine therapy - O. I., Zaid; Abd. Majid, R.; Sidek, H. M.; S. M., Noor; Abd Rachman Isnadi, M. F.; Bello, R. O.; Chin, V. K.; Basir, R. (Malaysian Society of Parasitology and Tropical Medicine, 2020)
Treatment Failure with chloroquine is one of the challenges that faced the dedicated efforts to eradicate malaria This study aims at investigating the impact of treatment failure with chloroquine on the progression of the disease-induced histo-pathogenic and immunogenic outcomes. To achieve this, Rane's protocol with modifications was applied on a model of Plasmodium berghei ANKA infected ICR mice to determine the dose response curve of chloroquine and to screen the treatment impact on the disease progression. Chloroquine was given at 1, 5, 10, 15 and 20 mg/kg once the parasitemia reached to 20-30% (the experimental initiation point). During the subsequent days, the mice were monitored for changes in the clinical signs, hematology parameters and the progress of the parasitemia until the parasitemia reached to 60-70% (the experimental termination point) or up to 10 days after chloroquine administration in case of achieving a complete eradication of the parasite. At the end, the mice were exsanguinated and their blood and organs were collected for the biochemistry and the histology study. A complete eradication of the parasite was achieved at 20 mg/kg while recrudescence was observed at the lower doses. At 1 mg/kg, the parasite growth was comparable to that of the positive control. The histo-pathogenic and immunogenic changes were stronger in the groups that experienced recrudescence (at 5 and 10 mg/kg). All in all, the study highlights the possibility of having a worsened clinical condition when chloroquine is given at its sub-therapeutic doses during malaria treatment.